How can we mainstream mental health in research engaging the range of Sustainable Development Goals? A theory of change. - Anna Madill; Poornima Bhola; Erminia Colucci; Karina Croucher; Adrian Evans; Rebecca Graber (Public Library of Science (PLoS), 2022)
Mental health is a leading cause of ill-health worldwide, disproportionately affects low-and-middle-income countries and, increasingly, is considered relevant across the Sustainable Development Goals (SDGs). Hence, we ask: How can we mainstream mental health in research engaging the range of SDGs? We use the UK Research and Innovation Global Challenges Research Fund (GCRF) as a case study. In a previous scoping review, we purposefully sampled non-mental health focused GCRF grants for diversity from 2015 until May-end 2020 (N = 36). In the present study, the principal investigator of each grant in this sample was invited to interview (11 accepting). Snowballing, our networks, and returning to the funding archive secured a further 15 interviews sampled for diversity (Final sample: 13 UK researchers and 13 of their overseas collaborators). A thematic analysis of this data organised key information into a trajectory from the challenges of incorporating mental health impact, to how these challenges might be overcome and, finally, to support needs. This analysis was then organised into a Theory of Change designed to promote the mainstreaming of mental health in global challenges research. We outline the implications for global challenges researchers, mental health practitioners, and global challenge research funders. One important implication is that we provide evidence to encourage funders to engage with the desire of researchers to contribute more broadly to the wellbeing of the communities with whom they work.